The Skandapurāṇa Volume IV Adhyāyas 70 - 95. Start of the Skanda and Andhaka Cycles - Bisschop, Peter (Groningen Oriental Studies, 2018)
Skandapurāṇa IV presents a critical edition of Adhyāyas 70-95 from the Skandapurāṇa , with an introduction and annotated English synopsis. The text edited in this volume includes the myths of Viṣṇu's manifestation as the Man-Lion (Narasiṃha), the birth of Skanda, the birth of Andhaka, and Hiraṇyākṣa's battle with the gods culminating in his victory and capture of the Earth. Thanks to generous support of the J. Gonda Fund Foundation, the e-book version of this volume is available in Open Access.